ANALISIS KINERJA PETUGAS PELAYANAN PADA PEMERIKSAAN KUALITAS AIR BERSIH DI UPTD LABORATORIUM KESEHATAN KABUPATEN TEMANGGUNG - Aris Suprianto; Priyastiwi Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to analyze the performance of service workers in checking the quality of clean water at the UPTD Health Laboratory in Temanggung Regency. The research was carried out starting in October 2022. This type of research is descriptive qualitative. Collection of interview and observation data. Miles and Huberman Model data analysis. The results of the study were obtained: 1) The performance of service workers at the UPTD Health Laboratory of Temanggung Regency was not optimal due to: limited ability of officers, facilities for submitting customer complaints were not well organized, many officers held concurrent other duties, lack of facilities and infrastructure, officers did not understand SOP and frequent incidents officer turnover. 2) Efforts to improve the performance of service workers at the UPTD Health Laboratory of Temanggung Regency, namely: providing facilities to officers related to training, seminars, workshops and or taking further studies in accordance with their respective professions, consulting the Health Service regarding constraints in the health laboratory, improving budgeting funds for improving facilities and infrastructure, making agreements with replacement officers if at any time the scheduled officers leave, carrying out routine monitoring and evaluation.